EMPLOYEES' WORK EFFICIENCY OF WYNDHAM GRAND PHUKET KALIM BAY, PHUKET PROVINCE - Chaioonkaew, Thongthon; Phongpaew, Aniruth; Sookchokenithiphokin , Thanatnan (Journal of MCU Phetchaburi Review, 2025)
The objectives of this research are 1) to examine Motivating factors in work performance and the work efficiency of the employees 2) to compare the work efficiency of the employees with the characteristics of the employees 3) To study the work motivation factors that affect the work efficiency of the employees. The sample group consisted of 200 employees. The instrument employed was a questionnaire. Used in data analysis include mean, standard deviation, t-test, F-test, and multiple regression analysis. The results of the research found that 1) Motivating factors in Work overall and in each aspect has the highest average level.. 2) The performance of employees as a whole and in each aspect is at the highest average level.. 3) Employees with differences in genders, ages, education levels, status, average monthly income and different job positions there was no effect on the work performance of employees in Wyndham Grand Phuket Kalim Bay Hotel, Phuket Province with statistically significant at the 0.05 level 4) factors for work performance, consisting of work characteristics, work policies, relationships with co-workers and supervisors, compensation and benefits, opportunities for career advancement, working environment and social conditions affecting the work efficiency of employees. And all 6 factors can explain the change in performance variability of employees at 65.40 percent.